International Journal of Mental Health Systems - Minas, Harry
International Journal of Mental Health Systems (IJMHS) publishes the latest mental health research and health systems research, reviews, case studies and guidelines, policy, debates, technical and methodological advances, and lessons from the field that will advance and shape the emerging discipline of global mental health. Advances in understanding of, and treatments for, mental illness frequently do not benefit those who most need them because of poorly developed mental health systems. Globally there is increasing attention to mental health legislation and policy, mental health system financing and governance, mental health service design implementation and evaluation, human resource development, effective translation of research to inform mental health policies and programs. IJMHS is committed to promotion and protection of the human rights of people with mental illness.